Color Illustration of Diagnosis and Control for Modern Sugarcane Diseases, Pests, and Weeds - Huang, Ying-Kun (Springer Singapore, 2018)
This book systematically presents 40 pests, 7 natural pest enemies, and 20 diseases and weeds commonly encountered in sugarcane production, combining clear colour photos with detailed scientific descriptions. It covers a range of related topics, including morphological identification, habits and frequency of occurrence, prevention and control measures, symptom identification, characteristics of infections and epidemics, parasitic (predator) characteristics, ways of utilising natural pest enemies, main species and distribution, fluctuation in the field, and chemical control of weeds. With novel content presented in simple, straightforward language, the book provides a valuable reference guide for scientific researchers, educators and industrial practitioners, as well as students and advisers at agricultural universities.